PROGNOSTIC FACTORS OF RENAL CANCER - Kurnia, Riyan Adi; Warli, Syah Mirsya; Siregar, Ginanda Putra (Indonesian Journal of Urology, 2017)
Objective: Course of the disease of kidney cancer may be unpredictable. For example, between 4.2–7.1% of patients with tumours ≤4 cm that are usually slow-growing may have metastases at diagnostic and are at an elevated risk of disease-specific mortality. Conversely, as many as 40% of patients with lymph node metastases were diagnosed at nephrectomy are alive 5 year after surgery. Several approaches have been proposed to help predict the course of disease of kidney cancer and to distinguish between poor and favourable risk patients. In this study, we review the existing prognostic factors and compared with established prognostic models. Material & methods: This is an analytic descriptive study of all kidney cancer patients treated at Haji Adam Malik Hospital between 2011 and 2015. Individual patient data was collected from medical record and compiled. Results: The number of samples analyzed in this study were 38 patients. We found seven patients remain alive of the entire sample. From the results of the univariate test, the factors that have a significant relationship with the mortality rate were low KPS (<80), weight loss, and nephrectomy. From the results of multivariate analysis, nephrectomy is the only prognostic factor in patients with kidney cancer. Mortality rate was 0.056x lower in patients who underwent nephrectomy compared with patients who did not underwent nephrectomy. Conclusion: Despite the high mortality rate that is found in this study, nephrectomy still has a place in kidney cancer management, even in patients with advanced stage.